Influence of artificial reefs on fish assemblage of the Barra Bonita Reservoir (São Paulo, Brazil) - Freitas, Carlos E. C.; Petrere Jr., Miguel [UNESP] (Wiley, 2001)
This paper deals with the effects of introduced artificial reefs on the diversity of freshwater fish communities in lentic and lotic zones of a very impacted river in southeastern Brazil. To accomplish this goal, artificial reefs were introduced, in December 1997, in the Barra Bonita reservoir and in the lotic zone immediately below the dam. Fish diversity was always higher in the lotic zone than in the reservoir. Accordingly, fish diversity near the artificial reefs was consistently higher than in the control areas. We propose that the higher environmental complexity in the lotic zone, as compared to the reservoir, is incremented in areas where artificial reefs were introduced; also, we present that, in both areas, diversity is mainly affected by the introduction of artificial reefs.
Keywords: Artificial reefs; Diversity; Fish assemblages; artificial reef; community composition; fish; lotic environment; species diversity; Brazil